BUILDING DISTRIBUTED APPLICATIONS TO CALCULATE COURSE LEARNING OUTCOMES - Triyono, Joko; Setyowati, Dwi; Tefa, Robertus; Marsadualan, Agus (Universitas Aisyiyah Surakarta, 2024)
Information technology has become an inseparable part of everyday life, as well as in the professional activities of lecturers. In basic concepts, information will follow a pattern starting from input – process and output, so that the quality of information will depend on the quality of incoming input. In the field of academic activities, the relationship between data is very much, and each of these data binds each other and influences each other. With the complexity of activities in the academic field and various problems that arise, so that activities in the academic field appear many information systems that are sometimes not related between each information system. Specific cases from sections in the academic field, for example, in analyzing the results of learning activities that are always carried out at the end of each semester in the form of course learning outcomes, lecturers will always carry out these activities at the end of each semester, with data sources in the form of curriculum, RPS and student grades, lecturers will calculate to produce information on the results of learning activities. The result of this study is a web application architecture design model so that a distributed application can be used by departments and lecturers to calculate the learning outcomes of courses that are simpler and more effective